BOEZEM WONOREJO RUNGKUT DI GUNUNG ANYAR SEBAGAI ALTERNATIF PENGENDALI BANJIR DI WILAYAH SURABAYA SELATAN - Kusnan Kusnan (Fakultas Teknik , Universitas PGRI Adi Buana Surabaya, 2012)
Surabaya as the Capital of East Java Province is a settlement area and also as the centers of Industry, Trade, Service, Education. Due to the development of all activities lines grow rapidly, including the supplying of housing, industrial plants, thus automatically they change the land functions (land use), and the river functions formerly as the irrigation but now changed to be the drainage, causing the increasingly large of flow coefficient, also increasingly large the surface overflow discharge. With the changes, they change irrigation canal functions become the drainage, that bring the river constriction impact, that the river no longer able to hold and channeling flood discharge both come from the upper course, and due to the local rainfall occurred continually in the dry season, water will overflow to flood the areas with the low elevation under sea level, causing the prolonged water backup, as a result, disturb the economy wheel circulation, causing the big losses. To overcome backup water many things we can perform, such as waterworks widening, sediment dredging, and the making of dike heightening, waterway diversion. By the consideration that costing is expensive and the difficult of area (land) deliverance at the settlement area in order to overcome the water backup/flood, then the solution as alternative can be taken is revitalization of Wonorejo Boezem in Gunung Anyar of Rungkut area, where its land is not productive (non productive fishpond area) with the shallow condition. Instead of revitalization, it is also developed the new construction or enlargement of reservoir capacity in the Boezem. From the results of this research consistent with the work items result in as follows: Sum the design flow discharge as much as 51.4863 m3/s(C.I.A)+0,446 (gross water discharge people) + 0.3327 m3s (gross water discharge Industry) = 52.165 m3/s with the repeated period scale of 10 years, while the reservoir discharge capacity of Wonorejo Boezem as much as less than 570,874 m3 need th design flow discharge as much as 586.000 mÂ³s and the drainage flowing water to the Boezem, the drainage dike height is 1.50 m with water level of 1.25 meters and wide 28 meters, then in order to suppress the budget costing for flood control in Southern Surabaya Area, as the alternative is by function maximally on the Wonorejo Boezem reservoir, still sufficiently can overcome flood.